2006
DOI: 10.1308/135576106776337841
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Written Reports Provided by Consultants in Restorative Dentistry to Referring General Dental Practitioners in the West Midlands

Abstract: The GDPs who responded to the questionnaires felt that a bullet point format or summary style report from the consultants concerned would summarise cases more clearly and concisely than the conventional standard format letters which they had previously received. Opportunities may exist for improving the quality of consultant reply letters through the use of structured templates and/or a summary or bullet point format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Studies have shown that factors such as the color of text, word choice, and font style all affect processing fluency and thus shape individuals’ ability and understand the information they receive (Rennekamp ; Song and Schwarz 2006; Whittlesea ). Similar findings in the medical sciences reveal that some methods of structuring medical reports make it easier for the lay public to learn about complex health issues than others (Saha and Summerwill ). The key conclusion is that fluent methods of information presentation tend to improve citizens’ ability to use the information communicated to them (Miele and Molden ).…”
Section: Linking Policy Transparency To Policy Understandingmentioning
confidence: 61%
See 1 more Smart Citation
“…Studies have shown that factors such as the color of text, word choice, and font style all affect processing fluency and thus shape individuals’ ability and understand the information they receive (Rennekamp ; Song and Schwarz 2006; Whittlesea ). Similar findings in the medical sciences reveal that some methods of structuring medical reports make it easier for the lay public to learn about complex health issues than others (Saha and Summerwill ). The key conclusion is that fluent methods of information presentation tend to improve citizens’ ability to use the information communicated to them (Miele and Molden ).…”
Section: Linking Policy Transparency To Policy Understandingmentioning
confidence: 61%
“…The key conclusion is that fluent methods of information presentation tend to improve citizens’ ability to use the information communicated to them (Miele and Molden ). By rendering information more usable, enhancing the processing fluency of a message also improves individuals’ ability to understand the information they are exposed to (Paas, Renkl, and Sweller ; Saha and Summerwill ). This is because improving fluency makes it easier for individuals to sift through noise and pick up on the signal of interest (Sweller ).
Hypothesis 1 : Policy information presented in a high‐fluency format will be better understood than information presented in a low‐fluency format.
…”
Section: Linking Policy Transparency To Policy Understandingmentioning
confidence: 99%
“…This leaves no room for the health worker to use his or her discretion as to what variable to fill in and what not to for each patient. Although one study33 showed that a letter with formatted content has the potential to enhance the quality of referral letters, other studies23 37 showed that general practitioners preferred to have referral forms with less required items and would rather write a summary based on what they consider important for each patient rather than fill a form with mandatory fields. In that same study in Australia,33 eight items were rated as essential information by a majority of referral letter recipients who are practitioners, and these include the diagnosis, clinical findings, test results, treatment options and recommendations, and prognosis.…”
Section: Discussionmentioning
confidence: 99%